Structural acoustic controlled active micro-perforated panel absorber for improving wide-band low frequency sound absorption. (1st October 2022) - Ma, Xiyue; Yurchenko, Daniil; Chen, Kean; Wang, Lei; Liu, Yang; Yang, Kai
Abstract: This paper investigates the performance of the structural acoustic controlled active micro-perforated panel absorber (SAC-AMPPA), which can achieve wide-band perfect low frequency sound absorption (absorption coefficient is close to 1). The SAC-AMPPA applies point force-controlled backing panel to actively improve the low-frequency sound absorption of the MPPA with the purpose of saving space to suit it better for applications. The theoretical model of the SAC-AMPPA is firstly established using the modal analysis approach. Influence of structure size and point force position on sound absorption performance is explored. Then, the experimental tests were performed to validate the theoretical modeling and findings. Finally, the physical mechanisms of active control are analyzed in detail and some physical insights are summarized. Simplified error sensing strategy for small sized SAC-AMPPA is also constructed. Results obtained show that the preconditions of the point force locating at the center of the backing panel or relatively small sized SAC-AMPPA can guarantee less cavity modes being excited and achieving perfect sound absorption in a very wide controllable bandwidth. The main reason of this lies in the key findings, i.e., except for the (0, 0, m ) mode, other cavity modes excited by the backing panel cannot contribute to the improvement of low-frequency sound absorption below their resonant frequencies. They radiate sound energy towards the outside of SAC-AMPPA and play a negative role above their resonant frequencies. Provided a uniform cavity sound field is guaranteed in controlled condition, the sound pressure release (PR) and impedance matching (IM) strategies can be used to conveniently construct error sensing strategy of the SAC-AMPPA.